PENGARUH LIMBAH INDUSTRI AGAR-AGAR RUMPUT LAUT TERHADAP SIFAT KIMIA TANAH DAN PERTUMBUHAN TANAMAN JAGUNG PADA TANAH INCEPTISOL KECAMATAN PANDAAN PASURUAN - Bambang Siswanto; Widowati Widowati (Universitas Tribhuwana Tunggadewi, 2018)
Inceptisol is one type of land order that is widely spread in Indonesia. Its distribution reaches approximately 52.0 million hectares (Kasno, 2009). Inceptisol is widely used as an intensive farm because its management is less precise, then most Inceptisol fertility rate becomes low. This is often shown by soil acidity, organic matter content, and low nitrogen, to improve such properties one of which can use the addition of organic matter. The problem that often arises is the high cost of organic fertilizer. Seaweed industry waste is a source of organic material that has not been widely utilized. Of the total raw materials processed, there is 65 to 70 percent of industrial products produced by the seaweed industry waste every day (Mandela. 2010). Usually these side products are only left to accumulate at the landfill site. Seaweed industry waste has the potential to be used as a source of soil organic matter because the organic material content of products of seaweed industry reaches 6.4% (Afif, 2011). The addition of nutrients to the application of inorganic materials is considered as an alternative step in increasing crop productivity. Based on the description above, it is necessary to conduct research to utilize the waste of seaweed industry, to get high corn production in Inceptisol. The objectives of this research are: (1) To know the effect of seaweed industrial solid waste on soil chemical properties Inceptisol and (2) growth of maize. The research was conducted in the greenhouse, while for the analysis of soil samples and the waste of seaweed industry was conducted in soil chemistry and soil physics laboratory, Department of Soil Science, Faculty of Agriculture, Brawijaya Universities. The study was conducted from May to August 2016. The soil samples used in this study were taken from Kemirisewu village, Pandaan sub-district, Pasuruan district at a depth of 0-20 cm. The waste of seaweed gel plant is obtained from PT. HAKIKI DONARTA, Pandaan Sub-district, Pasuruan Regency. The basic fertilizers used are Urea, KCl, and TSP. Maize seeds used as indicator plants are hybrid varieties of BISI-2 maize. This study used Completely Randomized Design (RAL) with 4 (four) treatments and 3 (three) replications. Addition of solid waste of seaweed with the dosage of 15 Mg/ha, increased of soil acidity and C-Organic content, besides also can increase Phosphorus and Potassium content available, Nitrogen, Phosphorus, and Potassium plant uptake, and the best growth of maize.